Determinants of Subnational Own-Source Revenue Performance: A Six-Cluster Analysis of East Java, Indonesia - Muhammad Salam Taufiqi; Sri Mulatsih; Hendro Sasongko (Universitas KH. Abdul Chalim Mojokerto, 2026)
East Java Province shows a high degree of dependency of central government control for fiscal regional autonomy. This paper discusses the attributes of Original Regional Revenue (PAD) across the 38 districts and cities within East Java for the periods 2020–2024. This makes use of a six-cluster geomapping strategy and other relevant economical and cultural methodologies. From a descriptive and statistical approach on BPS & DJPK datasets contrasted with PAD and fiscal spending and welfare variables, the clusters revealed substantial divergence. The Industrial Cluster of Surabaya has the highest PAD and the Madura Cluster is consistently rated lowest. Unlike the other Pandemics, COVID-19 effects were delayed with a substantial drop in 2022, and not in 2020 and 2021. While the pandemic revitalized the industrial areas, it did less for the tourism-dependent areas. Rapid tourism development during the pandemic did not help. PAD growth was also influenced by the development of the South Cross Road. With the shift of focus of the gap in financing the urban and rural areas to the insatiable needs for alternative revenue sources, the self-financing mechanisms that regional autonomy provides for the areas to manage their finances sustainably are being strengthened.